The communicative aspect of burial mound symbolism. A commentary to Homer’s accounts - Mierzwiński, Andrzej (Institute of Archaeology Rzeszów University, 2013)
In archaeological discussions one may observe two fundamental and complementary aspects of burial mound symbolism – cosmological and sociological. In the first instance the process of building the mound represents a ritual reconstruction of the world’s structure. In the other instance it attests to the hierarchical ordering of the community. The complementarity with regard to the cosmological aspect means that the range and structure of the community transcends the borders of temporality. There is one other aspect, however, which could be labeled as the ‘communicative aspect’. It confirms the symbolic ‘inscribing’ of the dead into the cosmic and social order and their active role in sustaining the functioning and integrity of various spheres of existence. In consequence, the memory of the dead ancestors was guaranteed and the respect towards the deceased was not only an obligation dictated by the gods, but it also remained something for which the living constantly cared. This relative sense of human existence may be encountered in Homeric eschatology.
Komunikacyjny aspekt symboliki kurhanu. Komentarz do przekazów Homera
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; burial mound; the deceased; funerary ritual; communication; memory; Homeric eschatology